Manliness and its discontents : the Black middle class and the transformation of masculinity, 1900-1930 - Summers, Martin Anthony (Gender & American culture., 2004)
In a pathbreaking new assessment of the shaping of black male identity in the early twentieth century, Martin Summers explores how middle-class African American and African Caribbean immigrant men constructed a gendered sense of self through organizational life, work, leisure, and cultural production.